Vascular malformations of the spinal - Gastelumendi, René (1956)
Within the central nervous system pathology, vascular abnormalities offer many problems of interest, particularly with respect to its core location. In general. to treat vascular disease has been given short shrift to the bone and yet vascular abnormalities of this organ, especially venous, are known from nearly a century and having considered simple anatomical curiosities. So we thought of interest to present some case studies over the past five years.